Feeding effects of cottonseed and its co-products on the meat proteome from ram lambs - Paim, Tiago do Prado (2019)
Gossypol easily pairs with lysine side chains and enzymes involved in the cellular growth process. The effect of gossypol (a compound present in cotton co-products) in ruminant metabolism and meat quality is not yet clear. This study was undertaken in order to evaluate the effects of cotton co-products in lamb muscle proteome. Twenty-four Santa Inês ram lambs, 5-months old (20.6 ± 1.9 kg), were randomly assigned to four treatments: control (without cottonseed), whole cottonseed, cottonseed meal and high oil cottonseed meal. At 95 days into the experiment, lambs were slaughtered and samples from Longissimus dorsi were collected. Proteins were extracted and analyzed by 2-D electrophoresis. Spots showing a significant effect from the treatment (the “treatment effect”) and present in more than 90 % of the samples were identified using mass spectrometry. Cotton co-products decreased the abundance of aldehyde and malate dehydrogenases, creatine kinase M-type and Adenosine triphosphate (ATP) synthase. They also increased four proteins related to muscle contraction. Thus, feeding cotton co-products to lambs changed the abundance of important muscle proteins. A cotton co-product diet induced a negative impact on the energy supply of muscle cells and, consequently, the abundance of ATP dependent proteins (contractile apparatus) increased, probably in order to offset and maintain muscle function. These proteomic changes can promote our understanding of alterations in the sensorial properties of meat due to cotton co-product diets in further investigations.